(untitled) (Journal of Science, Technology and Innovation Policy, 2023)
Digital economy serves as one of the agenda of Association of Southeast Asian Nations (ASEAN) in undertaking the Fourth Industrial Revolution. Additionally, the Indonesian government is committed to conducting research and innovation related to digital economy. Therefore, this study aims to reveal trends and future research under the topic of digital economy in Indonesia. This study utilizes big data methods, conducted through Scopus database, while the analysis is conducted through bibliometrics and visualization VOSViewer. The results of this study indicate that financial technology becomes the most published topic by authors with affiliation from Indonesia, although the topic has been widely discussed in international journals. Meanwhile, future research topics include research on digital payments, technology acceptance for the Micro, small, and medium enterprises (MSMEs), digital transformation for e-learning, and e-government.